Carotid Endarterectomy Surgical Simulation Model Using a Bovine Placenta Vessel. Issue 5 (November 2015) - Belykh, Evgenii G.; Lei, Ting; Oliveira, Magaldi M.; Almefty, Rami O.; Yagmurlu, Kaan; Elhadi, Ali M.; Sun, Guozhu; Bichard, William D.; Spetzler, Robert F.; Preul, Mark C.; Nakaji, Peter
Abstract : BACKGROUND: Carotid endarterectomy (CEA) is a common, well-developed surgical procedure. Although surgical simulation is gaining in importance for residency training, CEA practice opportunities for surgical residents are limited. OBJECTIVE: To describe a new haptic CEA model. METHODS: Six bovine placentas were used to create the model. Each placenta provided about 6 large arterial and venous bifurcations. In total, 36 large-vessel bifurcations were dissected and prepared for the CEA simulation. Bovine placenta vessels were arranged to simulate the common carotid artery (CCA), internal carotid artery (ICA), and external carotid artery (ECA). The diameters and wall thicknesses were measured and compared with human CCA, ICA, and ECA parameters. RESULTS: All bovine placentas provided vessels suitable for modeling carotid artery bifurcations and CEA training. Mean ± SD diameters of simulated CCAs, ECAs, and ICAs were 11.2 ± 1.8, 4.3 ± 0.5, and 9.8 ± 3.0 mm, respectively, from nondilated veins and 8.7 ± 1.4, 4.4 ± 1.3, and 7.2 ± 1.7 mm, respectively, from nondilated arteries. Mean vessel wall thicknesses were 2.0 ± 0.6 mm for arteries and 1.4 ± 0.5 mm for veins. Placental vessel tissue had dimensions and handling characteristics similar to those of human carotid arteries. The CEA procedure and its subtasks, including vessel-tissue preparation and surgical skills performance, could be reproduced with high fidelity. CONCLUSION: A bovine placenta training model for CEA is inexpensive and readily available and closely resembles human carotid arteries. The model can provide a convenient and valuable simulation and practice addition for vascular surgery training. ABBREVIATIONS: CCA, common carotid artery CEA, carotid endarterectomy ECA, external carotid artery ICA, internal carotid artery